Case Report: QT Prolongation and Abortive Sudden Death Observed in an 85-Year-Old Female Patient With Advanced Lung Cancer Treated With Tyrosine Kinase Inhibitor Osimertinib - Kondo, Moë; Kisanuki, Megumi; Kokawa, Yosuke; Gohara, Seiichiro; Kawano, Osamu; Kagiyama, Shuntaro; Maruyama, Toru; Odashiro, Keita; Maehara, Yoshihiko (Frontiers in Cardiovascular Medicine, 2021)
Cardiac arrest occurred in an 85-year-old female administered osimertinib for advanced lung cancer expressing epidermal growth factor receptor (EGFR) mutations. Electrocardiogram (ECG) recorded at recurrence of spontaneous circulation showed sinus rhythm associated with mild QT prolongation (QTc = 455 msec) to which silent myocardial ischemia and coadministration of itraconazole and herbal drug causing hypokalemia (2.1 mEq/L) may have contributed. Discontinuation of osimertinib, itraconazole and herbal drug, potassium supplementation and percutaneous coronary intervention alleviated QT prolongation (QTc = 432 msec). Osimertinib is the third-generation tyrosine kinase inhibitor lengthening QT interval, and careful monitoring of ECG, serum potassium and drugs coadministered during chemotherapy including osimertinib are highly required.